2020
DOI: 10.1097/ijg.0000000000001595
|View full text |Cite
|
Sign up to set email alerts
|

Disc-fovea Angle Is Associated With Visual Field Defect Location in Patients With Glaucoma

Abstract: Precis: The current study showed that glaucomatous eyes from patients with central visual field defects presented less negative disc-fovea angle compared with patients with peripheral defects. Purpose: The purpose of this study was to investigate the relationship between disc-fovea angle and visual field defect location in patients with glaucoma. Materials and Methods: This was a cross-sectional study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…In our assessment, the average DFA found (-7.66° ± 3.40°) was higher than that found by other authors (11,14) , but between the evaluated groups (myopic vs. hyperopic), the DFA had no statistical difference. Also, comparing the groups with the highest and lowest DFA (Table 2), there was no significant association with the initial defect location.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In our assessment, the average DFA found (-7.66° ± 3.40°) was higher than that found by other authors (11,14) , but between the evaluated groups (myopic vs. hyperopic), the DFA had no statistical difference. Also, comparing the groups with the highest and lowest DFA (Table 2), there was no significant association with the initial defect location.…”
Section: Discussioncontrasting
confidence: 83%
“…Central scotomas can impact more intensely on daily activities and should be treated with greater rigor (11) . In our research, we had a greater number of scotomas in the superior hemicampus compared to the inferior hemicampus, especially when referring to central scotomas (4 inferior vs. 14 superior).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Abe et al suggested a less negative disc-fovea angle was associated with more advanced central visual field damage. 31 This was also observed in a separate study. 32 However, an epidemiological study in Japan showed no difference in the papillomacular bundle tilt angle between normative and glaucomatous eyes.…”
Section: Discussionsupporting
confidence: 73%